THE EFFECT OF GLYCEROL CONTENT ON PHYSICAL AND MECHANICAL PROPERTIES OF THE BIODEGRADABLE FILM FROM SWEET POTATO FLOUR FOR PRESERVING NAMWA BANANA: - - Theamdee, Pawinee; Auasalung, Thanyalak (Life Sciences and Environment Journal, 2019)
This research studied the effect of using glycerol as a plasticizer on physical and mechanical properties of a biodegradable film made from sweet potato flour. This film was coated on a fruit for a preserving purpose. The preparation of the film was done by dissolving sweet potato flour in water to the concentration of 5 wt% and the glycerol was added at 3 levels; 0, 30, and 60 wt%. The film was molded and dried at 60 oC for 18 h. The results showed that the thickness of the films, which increased with the increasing of the glycerol content, ranged between 0.34-0.39 mm. The sweet potato flour film had water vapor permeability value of 0.009-0.026 g/m2/kPa/h. The water permeability increased with the glycerol content. The tensile strength of the film dramatically decreased as a result of high glycerol content in the film. After the films were buried under the ground (8-10 cm depth) for 4 weeks, they were degraded by 16-55%. This degradation increased with the increasing of glycerol content. The films were used to preserve banana fruit. Coating the banana fruit with sweet potato film with 30% glycerol content showed the best on extending the shelf life for 3 days at room temperature. These results indicated that sweet potato flour biodegradable film could be used to preserve fruits. In addition, this made of natural film is biodegradable which can help reduce the amount of waste.